An Analysis of How the Fashion Industry Utilises Sustainable Design for Brand Positioning: A Rewoven Case Study - Lengane, Kgabane (The IIE, 2020)
The purpose of this study is to analyse which positioning strategies sustainable fashion brands in South Africa are using. Due to the ecological damage caused by the fashion industry, academia, governments, businesses and individuals are turning their attention towards sustainable solutions for the industry’s textile waste problem. Rewoven was chosen as the case study for this paper, due to it being the first South African brand that recycles textile waste to make clothing products. An interpretivist approach informed qualitative interviews with Rewoven Africa’s executives. Additionally, a thematic content analysis conducted on Rewoven’s and its competitors’ websites, enabled an understanding of how a South African fashion brand thinks about target markets, competition, differentiation and sustainable design when creating its brand positioning strategies. Ultimately, Keller’s Brand Positioning Model coupled with the design thinking methodology assisted the researcher to identify the two key elements of Rewoven’s brand positioning strategy, in relation to its functional and emotional attributes. Therefore, brands that are looking to build a sustainable fashion brand in South Africa, may find merit in following Keller’s brand positioning model and the design thinking approach to solving brand related challenges.
Keywords: Ecological damage; Sustainable living; Sustainability; Textile waste; Textile recycling; Sustainable fashion brand